Comparative study on protein polymerization in whole-wheat dough modified by transglutaminase and glucose oxidase. (April 2018) - Niu, Meng; Xiong, Licheng; Zhang, Binjia; Jia, Caihua; Zhao, Siming
Abstract: The impacts of transglutaminase (TG) and glucose oxidase (GOX) on the protein polymerization in whole-wheat dough (WWD) were investigated. The addition levels were 0.5, 1.5, 3.0, and 6.0 U/g (flour), respectively. Both TG and GOX enhanced dough strength by increasing the development time, stability, and resistance of WWD. A more continuous and compact dough structure was produced by the enzymes, and GOX resulted in thicker and stronger gluten strands than TG as indicated in dough microstructure graphs. GOX was more effective in promoting protein polymerization by showing more enhanced bands in protein electrophoresis patterns. Moreover, increased α-helix and β-sheet conformation by TG and GOX confirmed more polymerized gluten and stable secondary structure formed in WWD. By reducing free water, both enzymes increased the population of less-tightly bound water, indicating enhanced water availability to gluten. The results suggest that TG and GOX could enhance protein polymerization and gluten development in WWD; GOX was more efficient in inducing strengthened gluten network and increasing dough strength than TG. Highlights: Transglutaminase (TG) and glucose oxidase (GOX) modified whole-wheat dough (WWD). Both enzymes enhanced the development time, stability, and resistance of WWD. GOX induced stronger gluten strands and a higher degree of protein polymerization. Both enzymes resulted in more stable protein secondary conformations. Some of free water was transferred and bound in gluten network after enzyme addition.